Synthesis, Structure and Gas‐Phase Reactivity of a Silver Hydride Complex [Ag3(PPh2)2CH23(μ3‐H)(μ3‐Cl)]BF41. Issue 32 (21st June 2013) - Zavras, Athanasios; Khairallah, George N.; Connell, Timothy U.; White, Jonathan M.; Edwards, Alison J.; Donnelly, Paul S.; O'Hair, Richard A. J.
<x xml:space="preserve">Abstract</x> Mass spectrometry shows the way! MS analysis of silver salts treated with sodium borohydride in the presence of a bis(phosphino) ligand revealed the formation of novel silver hydride nanocluster cations instead of all silver nanocluster cations. This serendipitous discovery prompted the condensed‐phase synthesis, isolation, and characterization of [Ag3(Ph2P)2CH23(μ3‐H)(μ3‐Cl)]BF4⋅0.5 CHCl3.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>